Situational Strength Cues from Social Sources at Work: Relative Importance and Mediated Effects - Alaybek, Balca; Dalal, Reeshad S.; Sheng, Zitong; Morris, Alexander G.; Tomassetti, Alan J.; Holland, Samantha J. (Frontiers in Psychology, 2017)
Situational strength is considered one of the most important situational forces at work because it can attenuate the personality–performance relationship. Although organizational scholars have studied the consequences of situational strength, they have paid little attention to its antecedents. To address this gap, the current study focused on situational strength cues from different social sources as antecedents of overall situational strength at work. Specifically, we examined how employees combine situational strength cues emanating from three social sources (i.e., coworkers, the immediate supervisor, and top management). Based on field theory, we hypothesized that the effect of situational strength from coworkers and immediate supervisors (i.e., proximal sources of situational strength) on employees’ perceptions of overall situational strength on the job would be greater than the effect of situational strength from the top management (i.e., the distal source of situational strength). We also hypothesized that the effect of situational strength from the distal source would be mediated by the effects of situational strength from the proximal sources. Data from 363 full-time employees were collected at two time points with a cross-lagged panel design. The first hypothesis was supported for one of the two situational strength facets studied. The second hypothesis was fully supported.